Aqueous Zinc‐Ion Batteries: Unraveling the Dissolution‐Mediated Reaction Mechanism of α‐MnO2 Cathodes for Aqueous Zn‐Ion Batteries (Small 48/2020). Issue 48 (3rd December 2020) - Kim, Sung Joo; Wu, Daren; Sadique, Nahian; Quilty, Calvin D.; Wu, Lijun; Marschilok, Amy C.; Takeuchi, Kenneth J.; Takeuchi, Esther S.; Zhu, Yimei
Abstract : In article number 2005406, Esther S. Takeuchi, Yimei Zhu, and co‐workers demonstrate the dissolution‐mediated reaction mechanism of Zn/α‐MnO2 system for aqueous zinc‐ion batteries via transmission electron microscopy. It involves α‐MnO2 dissolution that activates the cell by inducing the reversible formation of Zn4 SO4 (OH)6 · x H2 O and ZnMn3 O7 ·3H2 O upon electrochemical cycling via (de‐)insertion of Mn and Zn ions.